Breakfast Box: An Effort to Develop Vocabulary Mastery - lestari, dewi (Lingual Journal of Language and Culture; Vol 7 No 1 (2019): Lingual: Journal of Language and Culture, 2019)
Vocabulary is difficult skill for students on SMP Muhammadiyah 2 Surakarta. The students usually tend to listen, speak, read, and write text based on their vocabulary mastering. Once they get difficulty in understanding text, they will lose their courage to do more instructions. In order to build or understand a simple sentence, they need to open dictionary per word. As a result, students will easily lose interest and motivation to learn more. This research is carried out in SMP Muhammadiyah 2 Surakarta. It is on Jl. Kerinci No. 15. The research is conducted from July until Agustus 2016. The subject of this research is the IX-D grade students of SMP Muhammadiyah 2 Surakarta. The researcher chooses class D because the students have difficulties in understanding text due to the lack of vocabularies. That is why the researcher decides to improve their mastery in vocabulary through “vocabulary breakfast box”. “Vocabulary Breakfast Box” is adapted from “Kotak Sarapan Pagi” which is mostly applied at elementary school learning. It is about a board which contains of several boxes. Each box has an assignment for each student. The assignment can be the same as or different from others. It depends on the students’ assessment. The assignment exists in a form of a small paper. It consists of questions about words, sentences or text comprehension. Each box has students’ number or name. So students won’t go wrong to take others’ assignment. By using “vocabulary breakfast box”, the learning process in class has become interesting and varieties. Students are excited to try new strategy with teacher and discuss its benefits and lacks after the activity. Their vocabulary mastery becomes improved and they are able to answer most questions in each skill because they have recognized the words on the text or dialogue. Keywords: improving, vocabulary, vocabulary breakfast box